2020
DOI: 10.3390/su12083420
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tea Tree Essential Oil (Melaleuca alternifolia) in Laying Hen’s Nutrition on Performance and Egg Fatty Acid Profile as a Promising Sustainable Organic Agricultural Tool

Abstract: The level of production in a variety of organic production systems is often lower than in other traditional production systems. In poultry production, there is also a direct negative effect of the small scale regarding sustainable organic poultry production. Regardless of differences between organic and conventional production systems, this experiment aimed to investigate the usage of tea tree Melaleuca alternifolia (Maiden and Betche) Cheel essential oils as a natural alternative to antibiotics in hen nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
2
22
0
2
Order By: Relevance
“…A system of organic production includes the uttermost application of renewable energy sources, safeguarding genetic diversity of the agroecosystem, conservation of the environment, and the reduction of all types of pollution caused by agricultural production to create conditions in which agricultural producers can satisfy their basic needs and make an adequate profit [1,2]. For all these reasons, the study of the organic food market is highly significant because of the great demand for these products, which correlates with consumers' increased awareness and their attentiveness to health and environmental concerns [8]. Furthermore, there are also differences in the purchasing power and lifestyle between groups of consumers who can and want to afford these products.…”
Section: Introductionmentioning
confidence: 99%
“…A system of organic production includes the uttermost application of renewable energy sources, safeguarding genetic diversity of the agroecosystem, conservation of the environment, and the reduction of all types of pollution caused by agricultural production to create conditions in which agricultural producers can satisfy their basic needs and make an adequate profit [1,2]. For all these reasons, the study of the organic food market is highly significant because of the great demand for these products, which correlates with consumers' increased awareness and their attentiveness to health and environmental concerns [8]. Furthermore, there are also differences in the purchasing power and lifestyle between groups of consumers who can and want to afford these products.…”
Section: Introductionmentioning
confidence: 99%
“…A Melaleuca ou Tea tree (Melaleuca alternifolia) é uma planta utilizada tradicionalmente e tem seu óleo essencial extraído por destilação a vapor das suas folhas, apresentando vários componentes químicos (aromadendreno, cadineno, cimeno, cineole, globulol, ledeno, limoneno, pineno, sabineno, terpineol, viridiflorol, entre outros) com fortes propriedades antissépticas e usado para combater infecções e fungos (Puvača et al, 2020). Os estudos sobre os mecanismos de ação antimicrobiana do óleo essencial de Melaleuca indicam que esse óleo essencial causa lise e perda da integridade da membrana das bactérias, devido à saída de íons e inibição da respiração (Carson et al, 2006).…”
Section: Resultsunclassified
“…Os estudos sobre os mecanismos de ação antimicrobiana do óleo essencial de Melaleuca indicam que esse óleo essencial causa lise e perda da integridade da membrana das bactérias, devido à saída de íons e inibição da respiração (Carson et al, 2006). Diversos estudos mostram a redução do número de bactérias, quando linhagens foram submetidas aos vapores de óleos essenciais, durante a desinfecção de ambientes fechados, bem como nos sistemas de ventilação (Pibiri et al, 2006;Puvača et al, 2020).…”
Section: Resultsunclassified
“…Broiler fed with essential oil in diet exhibited increased T-SOD and T-AOC levels, but down-regulation of MDA concentration has been reported [49][50]. Puvaca et al [51] reported that diet supplemented with TTO improve the anti-oxidative ability of laying hens by increasing SOD and GSH-Px activities. Supplementation of animal diets with essential oil to fed can improve the antioxidant status of the animal body and increase meat quality [52].…”
Section: Antioxidant Statusmentioning
confidence: 99%